(untitled) (Journal of Applied Learning and Teaching, 2021)
The United Theory of Acceptance and Use of Technology (UTAUT) model has been widely used to study new technological systems and has proven to be a robust theoretical framework for predicting system intentional use. Many of the UTAUT studies have focused on educational technologies like learning management systems, mobile learning, instructional devices, online collaboration tools and educational services. This paper reviews previous work done on the UTAUT model and proposes an extended model to study educational technology acceptance by introducing additional constructs like usability, learnability and attitude.